2019
DOI: 10.1101/799320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Priming enables a NEK7-independent route of NLRP3 activation

Abstract: The NLRP3 inflammasome plays a central role in antimicrobial defense, as well as in sterile inflammatory conditions. NLRP3 activity is governed by two independent signals. The first signal primes NLRP3, allowing it to respond to its activation signal. In the murine system, the mitotic spindle kinase NEK7 has been identified as a crucial factor in relaying the activation signal to NLRP3. Here we show that the requirement for NEK7 can be bypassed by TAK1-dependent post-translational priming. Under pro-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…These studies suggest NEK7 is involved primarily in NLRP3 activation but a recent preprint study by Schmacke et al. argues that NEK7 functions as an NLRP3 priming factor 83 . Importantly, this study also identified a NEK7‐independent mechanism of NLRP3 activation, involving TAK1‐driven posttranslational priming of NLRP3.…”
Section: Nek7mentioning
confidence: 63%
See 1 more Smart Citation
“…These studies suggest NEK7 is involved primarily in NLRP3 activation but a recent preprint study by Schmacke et al. argues that NEK7 functions as an NLRP3 priming factor 83 . Importantly, this study also identified a NEK7‐independent mechanism of NLRP3 activation, involving TAK1‐driven posttranslational priming of NLRP3.…”
Section: Nek7mentioning
confidence: 63%
“…The authors suggest that previous studies were conducted in murine models while their research utilized human induced pluripotent stem cell‐derived Mϕs as the explanation for these differing results. This study highlights the complexity of NLRP3 regulation via NEK7 and the need for further investigation, particularly as determining the precise role played by NEK7 could identify it as a therapeutic target in NLRP3 inflammasome‐mediated diseases 83–86 …”
Section: Nek7mentioning
confidence: 93%
“…TAK1 kinase is described to regulate the canonical NLRP3 inflammasome at both priming and activation stages, by either mediating transcriptional priming through its role in NF-κB signalling downstream of TLR4 [46] or by controlling lysosomal rupture that leads to NLRP3 assembly and activation [38]. More recently, TAK1 has been suggested to mediate inflammasome activation via non transcriptional priming [40]. It was reported that the requirement for the NLRP3-binding protein NEK7 to form and active NLRP3 inflammasome [39] can be bypassed via TAK1 mediated potential post translational priming of NLRP3 [40].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, TAK1 has been suggested to mediate inflammasome activation via non transcriptional priming [40]. It was reported that the requirement for the NLRP3-binding protein NEK7 to form and active NLRP3 inflammasome [39] can be bypassed via TAK1 mediated potential post translational priming of NLRP3 [40]. It is therefore not clear whether TAK1 plays a role in a setting where TLR4 is not engaged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation